Ejecución del proyecto Marcahuamachuco y su influencia en la demanda turística del sitito arqueológico, provincia Sánchez Carrión, al año 2015. - Baltonado Paredes, Fanny Stefany (2015)
This research study had as general objective to describe and support the influence of the Marcahumachuco project in tourism demand in the area of influence, for it has been formulated the research problem: How Execution Marcahuamachuco Project influences ? Tourism Demand archaeological site in the province of Sanchez Carrion, 2015 .As methodology, the techniques used in data collection are: document analysis, survey managers responsible for the areas of the Executive Unit whose samples consist of 07 heads and 89 visitors respectively. The results have been processed, calling the independent variable with 54.87 points and the dependent variable with 51.08 points; transeccional was used descriptive correlational design, which allowed the analysis and respective discussion. This will have achieved the objectives of research, and has proven the validity of the hypothesis: "The Execution of Marcahuamachuco Project influences positively on Tourism Demand archaeological site in the province Sánchez Carrión, 2015" . Finally they have formulated the conclusions and recommendations thereon. The main conclusion states that improvements in the archaeological site, infrastructure, signaling access and movement, as well as dissemination through various means, favorably influenced tourism demand in the last five years; observed an average rating of both variables "very good". The main recommendation to boost tourism demand proposes to make the following programs: dissemination and tourism marketing, training and human development for project workers and members of the surrounding community as well as improve the quality of tourism-related establishments